Silicone Doped Chitosan-Acrylamide Coencapsulated Urea Fertilizer: An Approach to Controlled Release Fertilizers - Sempeho Ibahati Siafu (Journal of Nanotechnology)
In the absence of special management practices, urea is known to undergo chemical transformations resulting in severe losses (≈60–70%) of total fertilizer applied. In an attempt to design urea controlled release fertilizers in order to counterbalance the 60–70% loss, urea was cross-linked with chitosan and acrylamide under refluxed in situ copolymerization technique; the procedures were repeated with silicone doping prior cross-linking with MBA. The particles were characterized with FTIR/ATR, EDX, XRD, and SEM. The IR bands observed within 3426–409 cm−1 revealed the formation of new bands after coencapsulation for the νγN-H, νβN-H, νOH, νsNH2, νCH2, νC=O, δ′NH2, νC=C, δNH2, νC-N, βCH3, $C-N, γNH2, νC=O, and $CH2. Crystallinity indices for urea with and without silicone doping were found to be 50.9% and 72.1%, respectively, with a distinctive split peak at (d) 12.30°. The formation of Microdunes and Microballs 3D network sized 0.64 μm was noted. Release profiles demonstrated that 80% N was released in a period of 30 days at RT and pH 7. The release patterns exhibited linear and deformed sigmoid release models. Empirically, the findings demonstrated that it is possible to design urea controlled release fertilizers with varying particle sizes and morphologies by using chitosan-acrylamide coencapsulation.